HOPE FROM THE ASHES: A TRAUMA-HERMENEUTIC READING OF LAMENTATIONS 3 IN THE CONTEXT OF COLLECTIVE CRISIS - Alvin Budiman Kristian (STAK Reformed Remnant Internasional, 2026)
Issues ranging from post-pandemic trauma to escalating global violence have triggered a spiritual silence and a theological crisis regarding the existence of God. This article aims to formulate a grounded theology of hope through a trauma-hermeneutic reading of Lamentations 3. Employing a qualitative-interpretative method that analyzes poetic structure and transitions, the research reveals that the triple alphabetic acrostic structure of Lamentations 3 is not merely a literary device but an instrument of cognitive containment that organizes the chaos of traumatic experience. The study’s novelty lies in positioning verses 21–22 as a *locus theologicus*, where wounds are understood not as the absence of God, but as a revelatory space for divine *hesed* (steadfast love) at work